Multi-institutional comparison of simulated treatment delivery errors in ssIMRT, manually planned VMAT and autoplan-VMAT plans for nasopharyngeal radiotherapy. (October 2017) - Pogson, Elise M.; Aruguman, Sankar; Hansen, Christian R.; Currie, Michael; Oborn, Bradley M.; Blake, Samuel J.; Juresic, Josip; Ochoa, Cesar; Yakobi, Jim; Haman, Alicia; Trtovac, Admir; Carolan, Martin; et al.
Graphical abstract: Highlights: Clinically significant error magnitudes were found for 3 institutions/techniques. Collimator, gantry, MLC shift and MLC field size error impact was quantified. Large dose variations from simulated errors increased with higher plan complexity. Ap-VMAT resulted in greater complexity and dose variation than mp-VMAT plans. Various error metric response trends were consistent over institutions/techniques. Abstract: Purpose: To quantify the impact of simulated errors for nasopharynx radiotherapy across multiple institutions and planning techniques (auto-plan generated Volumetric Modulated Arc Therapy (ap-VMAT), manually planned VMAT (mp-VMAT) and manually planned step and shoot Intensity Modulated Radiation Therapy (mp-ssIMRT)). Methods: Ten patients were retrospectively planned with VMAT according to three institution's protocols. Within one institution two further treatment plans were generated using differing treatment planning techniques. This resulted in mp-ssIMRT, mp-VMAT, and ap-VMAT plans. Introduced treatment errors included Multi Leaf Collimator (MLC) shifts, MLC field size (MLCfs), gantry and collimator errors. A change of more than 5% in most selected dose metrics was considered to have potential clinical impact. The original patient plan total Monitor Units (MUs) were correlated to the total number of dose metrics exceeded. Results: The impact of different errors was consistent, with ap-VMAT plans (two institutions) showing larger dose deviations than mp-VMAT created plans (one institution). Across all institutions' VMAT plans the significant errors included; ±5° for the collimator angle, ±5 mm for the MLC shift and +1, ±2 and ±5 mm for the MLC field size. The total number of dose metrics exceeding tolerance was positively correlated to the VMAT total plan MUs (r = 0.51, p < 0.001), across all institutions and techniques. Conclusions: Differences in VMAT robustness to simulated errors across institutions occurred due to planning method differences. Whilst ap-VMAT was most sensitive to MLC errors, it also produced the best quality treatment plans. Mp-ssIMRT was most robust to errors. Higher VMAT treatment plan complexity led to less robust plans.